Inelastic deformation of plasma polymerised thin films facilitated by transient dense plasma focus irradiation. (12th September 2017) - Grant, Daniel S; Rawat, Rajdeep S; Bazaka, Kateryna; Jacob, Mohan V
Abstract: The high degree of crosslinking present in plasma polymerised thin films, coupled with their high molecular weight, imbues these films with properties similar to those of thermosetting polymers. For instance, such films tend to be relatively hard, insoluble, and to date have not exhibited plasticity when subjected to elevated temperatures. In this paper it is demonstrated that plasma polymers can, in fact, undergo plastic deformation in response to the application of extremely short-lived thermal treatment delivered by a dense plasma focus device, as evidenced by the evolution of bubble-like structures from the thin film. This finding suggests new avenues for texturing plasma thin films, and synthesising cavities that may find utility as thermal insulators or domains for material encapsulation.